8.4 M Deep Space Habitat– Medical Bay Concept Design and Human Factors Engineering Analysis - Mancl, Mary Claire Claire (Proceedings of the Wisconsin Space Conference, 2020)
Maintaining crew health throughout long duration deep space missions presents significant new design challenges. Since communication with Earth will be limited and it is not possible to return in the event of a medical emergency it is critical that medical care on a deep space mission be as autonomous as possible. The goal of this project was to design and assess a medical system concept for the Deep Space Habitat Concept Demonstrator derived from the core stage of the Space Launch System. The Medical Bay was designed as a primary location to support the medical care of 4 crew members on a 1000 day mission. It includes workspace, stowage, and direct access to all necessary medical equipment and supplies. A Human Factors Engineering (HFE) Analysis was conducted to test ergonomic effectiveness and system requirement compliance. This initial design will continue to be used by the HFE Team and the Advanced Concepts Office (ACO) at NASA’s Marshall Spaceflight Center (MSFC) for further demonstration, analysis, and design conception for deep space travel.